STUDI PEMANFAATAN AKTIVATOR LUMPUR AKTIF DAN EM4 DALAM PROSES PENGOMPOSAN LUMPUR ORGANIK, SAMPAH ORGANIK DOMESTIK, LIMBAH BAWANG MERAH GORENG DAN LIMBAH KULIT BAWANG - Ardhi Ristiawan (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Abstract In the process of waste water treatment produced a by-product in sludge. Sludge made a problem for the environment and for industry when no handling and processing. In this research is done using studies sludge become compost. Sludge mixed with rubbish organic domestic waste, waste of onion’s skin and fried onions waste. This study used activator EM4 and activator from activated sludge to optimize the composting process. The result showed that compost with activator EM4 likely matured faster because had the lower C/N ratio. Quality of compost on both activators have met the requirements of SNI 19-7030-2004 and did not shows significant differences. The best result at variations on activator em4 with ratio of organic sludge : rubbish domestic waste : onion’s skin waste : fried onions waste with % = 14: 3: 1: 1. Compost matured in the 3rd week with result (C-org 13.52; N = 0.85; P = 0.70; K = 0.58). In the same variation that used activator from activated sludge had a result (C-org = 16.96; N = 0.96; P = 0.80; K = 0.46). Based on these results, activated sludge can be used as an alternative activator in the composting process.